2020
DOI: 10.1080/17457823.2020.1788405
|View full text |Cite
|
Sign up to set email alerts
|

Reassembling teachers’ professional practice: an ethnography of intertextual hierarchies in primary mathematics

Abstract: The formation of teachers' professional practice has been discussed in relation to a wide variety of influences, with government prescription of practice often criticised as oppressing professional agency. Set within an ethnographic study within one English primary school, this paper explores the role of intertextuality in the form of intertextual hierarchies during a policyled period of change to teachers' professional practice: the introduction of a new way of teaching mathematics. Drawing on actor-network t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Firstly, there is a pressing need to re‐problematise established education policies which may otherwise maintain an authoritative and accepted presence in the knowledge base of the profession. Research examining how policy travels into practice has identified how certain policies infiltrate teachers' practices or ways of thinking, accepted as matter‐of‐fact ways of ‘doing things around here’, rather than held as problematised, fluid and contingent aspects of the social world (Unsworth & Tummons, 2021). In this sense, policy reifies, solidifies and sediments as positive entities of a particular notion, idea or practice, through usage within professional spaces and systems – performance‐related discussions based in teaching standards/ competencies policy, for example (Liew, 2012).…”
Section: Education Policy and The Immunisation Paradigmmentioning
confidence: 99%
“…Firstly, there is a pressing need to re‐problematise established education policies which may otherwise maintain an authoritative and accepted presence in the knowledge base of the profession. Research examining how policy travels into practice has identified how certain policies infiltrate teachers' practices or ways of thinking, accepted as matter‐of‐fact ways of ‘doing things around here’, rather than held as problematised, fluid and contingent aspects of the social world (Unsworth & Tummons, 2021). In this sense, policy reifies, solidifies and sediments as positive entities of a particular notion, idea or practice, through usage within professional spaces and systems – performance‐related discussions based in teaching standards/ competencies policy, for example (Liew, 2012).…”
Section: Education Policy and The Immunisation Paradigmmentioning
confidence: 99%
“…Unsworth and Tummons (2021) have spoken to limitations in the language and tools of ANT in describing how texts are used and created. We pointed out that many moments in the teachers' professional lives were centered around the creation and use of texts.…”
Section: An Ant‐ish Approachmentioning
confidence: 99%
“…In this article, I describe some of the challenges, successes, limitations, and lessons learned from these two semesters, analyze some of the pedagogical and logistical tradeoffs involved in virtual field school design, and sketch a variety of potential virtual field school models. As a case study in the anthropology of education more broadly, the article contributes an optimistic perspective to discussions of the relationship between internet‐based digital technologies, educational practices, and inequalities in access (Goode, 2010; Unsworth, 2023).…”
Section: Introductionmentioning
confidence: 99%